LIBRARY USERS’ SATISFACTION ANALYSIS USING SERVQUAL AND ANALYTIC NETWORK PROCESS - Hakim, Afif; Indah Pratiwi, Annisa; Lestari, Sri (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted at Library of University of Buana Perjuangan Karawang. The purpose of this study isto measure and analyze the level of satisfaction of library users with Servqual approach and prioritize the improvements that can be done by weighting of the criteria with ANP methode. The method used is the fivedimensional approach Servqual and weighting criteria with ANP. The conclusion shows that the average score for the criteria of reality is quite good (fairly satisfied) with the existing services at the Library of UBP Karawang, with an average score above 3, except for the criterion R4 (speed of turnitin service) average scores below 3 is 2.97, but because of the average expectation as well is not very high at 3.41 so that its gap is smaller than the gap between the expectations with the reality on the criteria E1 (the friendliness of the staff of the library) and E2 (the library staff willing to respond to complaints that exists). Except that, it was found that the three criteria of ranking the priority that should be the corrective action is E1 (the friendliness of the staff of the library), E2 (the library staff is willing to respond to complaints that exists), and T7 (a clear order information) with each of the priority value of 0.31; 0.31; and 0.27.